IMPLEMENTASI KESEHATAN, KECELAKAAN, DAN KESELAMATAN KERJA (K3) KARYAWAN PADA PT ALIS JAYA CIPTATAMA KLATEN - Puterisari, Dwi Utami; Wibawati, Latifah (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to analyze Occupational Health, Accidents, and Safety (K3) in employees at PT Alis Jaya Ciptatama Klaten. This research uses quantitative descriptive method. The population in this study were PT. Alis Jaya Ciptatama. The results showed an average value on the environmental conditions indicator of 3.40 including the strongly agreed category, the air regulation indicator of 3.05 including the agree category, the lighting regulation indicator of 3.09 including the category of agreeing, the indicator of work equipment use of 2.97 including agreeing, the indicator of physical and mental condition of employees of 2.21 including the category of disagreeing